The crystallin alpha B (HSPB5)-tripartite motif containing 33 (TRIM33) axis mediates myocardial fibrosis induced by angiotensinogen II through transforming growth factor-β (TGF-β1)-Smad3/4 signaling. Issue 4 (1st April 2022) - Wei, Tianwen; Du, Yingqiang; Shan, Tiankai; Chen, Jiawen; Shi, Dongwei; Yang, Tongtong; Wang, Jiankang; Zhang, Jun; Li, Yafei
ABSTRACT: Myocardial fibrosis, a common pathological manifestation of cardiac remodeling (CR), often leads to heart failure (HF) and even death. The underlying molecular mechanism of the role of TRIM33 in Ang II–induced myocardial fibrosis is not fully understood. We found that TRIM33 was specifically upregulated in CFs and myocardial tissue after Ang II stimulation. Adult mice induced by Ang II were used as in vivo models, and Ang II–induced neonatal mouse primary cardiac fibroblasts (CFs) were used as in vitro models. The level of CF fibrosis in vitro was assessed by CF proliferation, migration, activation and extracellular matrix (ECM) synthesis. In addition, Masson staining, the heart weight/body weight (HW/BW) ratio and echocardiography were used to evaluate the in vivo effect of TRIM33. TRIM33 expression was specifically upregulated in CFs and myocardial tissue after Ang II stimulation. In in vitro experiments, we found that TRIM33 knockdown promoted Ang II–induced CF proliferation, while TRIM33 overexpression weakened Ang II–induced CF proliferation, migration, activation and collagen synthesis. Mechanistically, we showed that TRIM33, negatively regulated by HSPB5, mediated its antifibrotic effect by inhibiting the activation of TGF-β1 and its downstream genes, Smad3 and Smad4. Finally, TRIM33 overexpression suppressed fibrosis and promoted cardiac repair and functional recovery in Ang II–induced mice. Our results clearly establish that TRIM33 limits cardiac fibrosis by hindering CF proliferation, migration, activation and collagen synthesis. Enhancing these beneficial functions of TRIM33 by a targeting vector might be a novel therapeutic strategy for CR. Graphical abstract: uf0001